Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen Bakso Cuanki Serayu Bandung, Indonesia - Putri Agustin Maimun (International Journal Administration, Business & Organization, 2022)
In the current culinary business competition, Bakso Cuanki Serayu must be able to compete with its competitors to maintain its existence because competition in the culinary world is getting tighter and makes consumer expectations increase. This study aims to determine how the effect of product quality on consumer satisfaction Bakso Cuanki Serayu Bandung. The study used a descriptive method with a quantitative approach. Data were collected using a questionnaire with a sample of 108 respondents. The data analysis method used is reliability test, descriptive analysis test, correlation test, normality test, linearity test, simple linear regression test, and coefficient of determination test using SPSS v.27 application. The results of this study indicate that there is a positive effect of product quality on consumer satisfaction in Bakso Cuanki Serayu.